2019
DOI: 10.1029/2018jb016907
|View full text |Cite
|
Sign up to set email alerts
|

Reevaluation of the Late Pleistocene Slip Rate of the Haiyuan Fault Near Songshan, Gansu Province, China

Abstract: Well-constrained fault slip rates are important for understanding strain partitioning within a fault system and the associated seismic hazard. The Haiyuan fault is a significant active strike-slip fault in the northeast margin of the Tibetan Plateau with ongoing controversy over its late Pleistocene slip rate. Previous work by Lasserre et al. (1999) suggested a slip rate of 12 ± 4 mm/year, which is higher than recent geodetically determined rates on adjacent fault sections. We reanalyze and reevaluate the slip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 84 publications
1
47
0
1
Order By: Relevance
“…We found that the largest slip rate is 6.6 mm/year and the average slip rate is 2.25 ± 2.24 mm/year. Although with large uncertainties, our estimated slip rate is less than the shallow creep rate of~5 mm/year from InSAR observations (Jolivet et al, 2013) and geological rate of 5-9 mm/year (Yao et al, 2019).…”
Section: The Characteristics Of Repeating Earthquakes At the Laohushamentioning
confidence: 58%
“…We found that the largest slip rate is 6.6 mm/year and the average slip rate is 2.25 ± 2.24 mm/year. Although with large uncertainties, our estimated slip rate is less than the shallow creep rate of~5 mm/year from InSAR observations (Jolivet et al, 2013) and geological rate of 5-9 mm/year (Yao et al, 2019).…”
Section: The Characteristics Of Repeating Earthquakes At the Laohushamentioning
confidence: 58%
“…Additionally, the fault planes of the two faults are steep (Li et al, 2013, 2017; Liu‐Zeng et al, 2007). The strain is then partitioned into left‐lateral shearing on the Qilian‐Haiyuan and Xiangshan‐Tianjingshan faults, and Qilian‐Haiyuan fault has a larger late Quaternary slip rate than Xiangshan‐Tianjianshan fault (Guo et al, 2017; Li et al, 2017; Yao et al, 2019; Zheng et al, 2013; Figure 17b).…”
Section: Discussionmentioning
confidence: 99%
“…Along the Maomao Shan segment, Lasserre et al (1999) determined a slip rate of 12 ± 4 mm/yr, while Yuan et al (1998) estimated lower slip rates of 4.1-5.4 mm/yr. Yao et al (2019) recently reassessed the offsets and age control for sites of Lasserre et al (1999) and updated the slip rate here to 5-8.9 mm/yr over the late Pleistocene -Holocene. Further east, the Haiyuan segment, which ruptured in the 1920 Haiyuan earthquake, was assigned a slip rate of 8 ± 2 mm/yr by Zhang et al (1988b).…”
Section: Geologic Settingmentioning
confidence: 99%